Robust quasi-time-optimal discrete-time sliding mode control of a servomechanism - Bayindir, M. I.; Can, H.; Akpolat, Z. H.; Ozdemir, M.; Akin, E. (Taylor & Francis Inc, 2007)
In this study, a new high-performance robust position control method is proposed. Robustness against system uncertainties is provided by discrete-time sliding mode control (DSMC) method. Quasi-optimal time-varying sliding surfaces are designed to ensure a high performance control. A new numerical method solving the time-optimal trajectory of the control system including friction is developed and implemented experimentally. Optimization of the system performance is aimed while the ranges of uncertainties and reference signals are kept as large as possible in a reasonable and practical manner. A new discount factor function especially determined for the investigated discrete-time control system is also proposed. Overshoots and oscillations that may occur in the case of high gain of switching function and large parameter variations are prevented. The proposed control method is applied to a vector controlled induction motor drive system. Experimental and simulation results showing the effects of the parameter variations and the wide range of the position reference on the system performance are presented.
Keywords: sliding mode control; position control; robust control; induction motor; PTOS; RQTOS